ANALYSIS OF THE FORMATION OF STUDENTS ' READING COMPREHENSION SKILLS IN THE LESSONS OF THE NATIVE LANGUAGE AND READING LITERACY - Abdijamilova Mahfuza Makhmudovna (Scholar Express Journal, 2023)
The article mainly describes the analysis of materials covering the reading comprehension processes of the native language and reading literacy textbooks in increasing reading literacy of Primary School students
Keywords: text; read understand; media text and media product